Atividade antimicrobiana, sinérgica e antibiofilme de sildenafil frente a Pseudomonas aeruginosa - Barin, Thais de Moraes (2021)
The increase in antimicrobial resistance has made the therapeutic armamentarium against bacterial infections increasingly scarce, generating a serious public health problem, especially in the hospital environment. In this context, serious infections caused by P. aeruginosa stand out, which include pneumonia, bloodstream infections, as well as infections associated with the use of medical devices due to the formation of biofilms. Thus, new therapeutic alternatives have been sought against the rise of resistant bacteria that cause persistent infections. In this sense, the repositioning of drugs emerges as a possible tool for the discovery of new compounds with antimicrobial action. The drug Sildenafil Citrate, commonly known as Viagra®, is currently used for the treatment of pulmonary hypertension. In this context, this study aimed to evaluate the antimicrobial, antibiofilm and synergistic activities of Sildenafil Citrate against P. aeruginosa. The antimicrobial activity was evaluated by microdilution in broth and showed that Sildenafil Citrate was capable of inhibiting bacterial growth. The antibiofilm action was evaluated on polystyrene plates using the crystal violet technique and also through Force Microscopy Atomic (MFA). The drug has been shown to be able to inhibit and destroy the biofilm, reducing total biomass by 87.17% to 83.81%, respectively. Atomic force microscopy indicated the positive action of Sildenafil in both destruction and inhibition of the biofilm. The trial of association of Sidenafil with the antimicrobials Cefepima Hydrochloride®, Imipenem® Monohydrate and Sodium Cilastatin and Polymyxin B® Sulfate, demonstrated a potentiating effect, resulting in a synergistic effect. Thus, the satisfactory results found in this study point to a new therapeutic use for the drug Sildenafil Citrate, making it a promising alternative for the treatment of infections caused by the pathogen P. aeruginosa.